Efficient capture of endocrine-disrupting compounds by a high-performance nanofiltration membrane for wastewater treatment. (1st December 2022) - Liu, Yanyan; Yuan, Shushan; Chi, Mingshuo; Wang, Yue; Van Eygen, Gilles; Zhao, Rui; Zhang, Xi; Li, Guichuan; Volodine, Alexander; Hu, Songqing; Zheng, Junfeng; Van der Bruggen, Bart
Highlights: The TFN-COF membrane combines advantages of NF membranes and adsorption materials. The TFN-COF membrane shows efficient capture of EDCs with high salt rejections. The mechanism of enhanced water flux and EDCs rejections are thoroughly explored. The TFN-COF membrane can be regenerated efficiently with ethanol washing. Abstract: Conventional polyamide (PA) nanofiltration (NF) membranes can readily adsorb aromatic compounds, such as endocrine disrupting compounds (EDCs). Therefore, these substances can easily be transported across the membrane by solution-diffusion, resulting in a poor EDC-rejection. In this work, a novel thin film nanocomposite (TFN) membrane was fabricated by incorporating covalent organic frameworks (COFs) into the PA layer via an interfacial polymerization reaction. COFs with functional groups can provide abundant active binding sites for highly efficient EDC-capture. The rejection of the optimal TFN-COF membrane for bisphenol A, bisphenol AF, and sodium 2-biphenylate was 98.3%, 99.1%, and 99.3%, respectively, which was much higher than of the rejection of the pristine NF-membrane (82.4%, 95.5%, and 96.4%, respectively). Additionally, the TFN-COF membrane could be regenerated fast and efficiently by washing with ethanol for some minutes. COF nanofillers with porous structures provide additional water channels, making it possible to overcome the permeability-selectivity trade-off of NF membranes. The water permeance (17.1 L m −2 h −1 bar −1 ) of the optimal membrane was about two times higher than for the pristine NF-membrane (8.7 L m −2 h −1 bar −1 ). In addition, the TFN-COF membrane with a COF-loading of 0.05% w/v had an excellent Na2 SO4 rejection (95.2%) due to size exclusion and strong Donnan effect. This work combines traditional NF membranes and adsorption materials to achieve efficient capture and rapid release of EDCs without sacrificing salt rejections, which opens the door to develop fit-for-purpose adsorptive NF membranes. Graphical abstract: Image, graphical abstract